2013
DOI: 10.1002/jbmr.1894
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Disease and Bisphosphonates Induce Osteonecrosis of the Jaws in Mice

Abstract: Osteonecrosis of the jaw (ONJ) is a well-recognized complication of antiresorptive medications, such as bisphosphonates (BPs). Although ONJ is most common after tooth extractions in patients receiving high dose BPs, many patients do not experience oral trauma. Animal models utilizing tooth extractions and high BP doses recapitulate several clinical, radiographic and histologic findings of ONJ. We and others have reported on rat models of ONJ utilizing experimental dental disease in the absence of tooth extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
147
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(167 citation statements)
references
References 62 publications
(156 reference statements)
15
147
1
4
Order By: Relevance
“…However, there is no standard BRONJ experimental model, since most models fail to reproduce clinical reality and do not associate several co-factors that undertake a reliable cause-effect relationship between Bps and disease pathogenesis. 6,7,8,9,15,16,17,18,19,20,21,22,23,24 To the best of our knowledge, this is the first study to demonstrate 100% of BRONJ-like lesions by associating tooth extractions with alendronate in cumulative dosages for the management of rheumatic diseases. 12 The first advantage of our experimental model is the high percentage of bone necrosis achieved.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, there is no standard BRONJ experimental model, since most models fail to reproduce clinical reality and do not associate several co-factors that undertake a reliable cause-effect relationship between Bps and disease pathogenesis. 6,7,8,9,15,16,17,18,19,20,21,22,23,24 To the best of our knowledge, this is the first study to demonstrate 100% of BRONJ-like lesions by associating tooth extractions with alendronate in cumulative dosages for the management of rheumatic diseases. 12 The first advantage of our experimental model is the high percentage of bone necrosis achieved.…”
Section: Discussionmentioning
confidence: 84%
“…12 The first advantage of our experimental model is the high percentage of bone necrosis achieved. The rate of bone lesions in previously published experimental models varies from 0 to 100%, 6,7,8,9,15,16,17,18,19,20,21,22,23,24 and only four papers have reported 100% of BRONJ-like lesions. 8,9,17,18 However, models that reported a bone lesion rate of 100% were developed by exposing animals to supra-therapeutic dose regimens 9,17 or to a high-intensity trauma, 8,18 which represents an artificial scenario.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they did not diagnose any ulcers or osteonecrosis. On the other hand, Kang et al (11) evaluated the effect of zoledronic acid on periapical lesions in rats and found BRONJ cases in these animals.…”
Section: Effect Of Zoledronic Acid In Periapical Lesionsmentioning
confidence: 99%